2008
DOI: 10.1016/j.expneurol.2007.06.020
|View full text |Cite
|
Sign up to set email alerts
|

The role of cyclic AMP signaling in promoting axonal regeneration after spinal cord injury

Abstract: The failure of axons to regenerate after spinal cord injury remains one of the greatest challenges facing both medicine and neuroscience, but in the last 20 years there have been tremendous advances in the field of spinal cord injury repair. One of the most important of these has been the identification of inhibitory proteins in CNS myelin, and this has led to the development of strategies that will enable axons to overcome myelin inhibition. Elevation of intracellular cyclic AMP (cAMP) has been one of the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
213
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(218 citation statements)
references
References 105 publications
(145 reference statements)
4
213
0
1
Order By: Relevance
“…2B,C), but cannot completely substitute for Ca 2ϩ (Fig. 3B) cAMP increases vesicular interactions in Golgi trafficking, growth cone extension, and transmitter release at synapses (Yoshihara et al, 2000;Sedej et al, 2005; for review see Hannila and Filbin, 2008). cAMP and cAMP activated proteins increase plasmalemmal sealing at PC times up to 20 min, including at 0 min PC, even when the bathing solution contains no Ca 2ϩ ( Fig.…”
Section: Model Of Plasmalemmal Sealingmentioning
confidence: 97%
“…2B,C), but cannot completely substitute for Ca 2ϩ (Fig. 3B) cAMP increases vesicular interactions in Golgi trafficking, growth cone extension, and transmitter release at synapses (Yoshihara et al, 2000;Sedej et al, 2005; for review see Hannila and Filbin, 2008). cAMP and cAMP activated proteins increase plasmalemmal sealing at PC times up to 20 min, including at 0 min PC, even when the bathing solution contains no Ca 2ϩ ( Fig.…”
Section: Model Of Plasmalemmal Sealingmentioning
confidence: 97%
“…Therefore, the potential PDE4 inhibitors may be an eicient alternative strategy to play antidepressant action especially in depressive disorder induced by inflammation. Consistent with this hypothesis, the previous studies have demonstrated that rolipram reduces neuroinflammation and promotes axonal regeneration and functional recuperation following spinal cord injury [96][97][98]; [62]. More evidence have shown that PDE4 inhibitor rolipram reduces the production of proinflammatory cytokines and modulates the activity of cAMP-mediated signaling and thus regulates CREB phosphorylation and the downstream efectors [99]; [62,68], showing that potential PDE4 inhibitors may be suitable to antagonize psychiatric disorders.…”
Section: Traditional Pde4 Inhibitorsmentioning
confidence: 70%
“…This work led to two streams of investigation, the second rather unresolved to this day: First, while mature axons can regrow, they do so at a disappointingly slow rate, and they lack the molecular components of young growing axons. Now we know that molecular brakes preventing mature axon regrowth include repressors of the m-TOR pathway, cAMP, and other transcription factors (Hannila and Filbin, 2008;Park et al, 2008). Second, we have long known that the environment of the site of injury, adult neuropil, and tracts are rife with glia that impede regrowth.…”
Section: When Things Go Wrong: What Have We Learned From Developmentamentioning
confidence: 99%